Percutaneous endoscopic lumbar discectomy for recurrent lumbar disc herniation. (March 2016) - Li, Xinhua; Hu, Zhouyang; Cui, Jian; Han, Yingchao; Pan, Jie; Yang, MingJie; Tan, Jun; Sun, Guixin; Li, Lijun
Abstract: The objective of this systematic review was to identify the effectiveness of percutaneous endoscopic lumbar discectomy (PELD) in the treatment of recurrent lumbar disc herniation (rLDH) and to present its indications and techniques. We conducted a comprehensive search in MEDLINE, EMBASE, PubMed, Web of Science and Cochrane databases, searching for relevant studies of managing rLDH with PELD up to July 2015. Only papers published in English were included. Two review authors independently selected the studies, extracted relevant data and assessed their methodological quality. The Cochrane Collaboration's Revman 5.3 software was used for data analyses among the controlled studies. At last, one randomized controlled trial (RCT), two non-randomized control studies and five observational studies including a total of 579 cases were selected for this system review. The methodological quality of these studies was low to modern. The mean overall improvement of leg pain (visual analogue scale) was 66.92% (50.6%–89.87%), back pain (visual analogue scale) 54.91% (29%–67.95%), Oswestry Disability Index 60.9% (40.7%–75%), global perceived effect (MacNab/other) 75.77% (60%–95%). The mean overall of complication rate was 4.89% (0%–9.76%), dural tear rate 0.1% (0%–4.9%), recurrence rate 6.3% (4%–10%), re-operation rate 3.66% (2.33%–4.8%). We conducted a meta-analysis among the control trials. Compared with Open discectomy (OD), PELD resulted in better outcomes in terms of operative time, blood loss, lower complication rates, but with no significance differences regarding hospital stay, second recurrence rate, Macnab criteria and pain reduction. In conclusion, according to the current evidence, PELD is an effective procedure for the treatment of rLDH in terms of reducing complication and shorting hospital course, comparing with OD. Therefore, we suggested that PELD was a feasible alternative to OD in the treatment of the rLDH in the condition of proper indication. High-quality RCTs with large sample sizes are needed to further confirm these results. Highlights: PELD is an effective procedure for rLDH in terms of reducing complication and shorting hospital course, comparing with OD. PELD was a feasible alternative to OD in the treatment of the rLDH. The indications and surgical techniques for PELD in the treatment of rLDH has been concluded.